A study on the spatial and temporal variability of the urban residential water consumption and its influencing factors in the major cities of China. (August 2018) - Lu, Shibao; Gao, Xuerui; Li, Wei; Jiang, Shuli; Huang, Li
Abstract: In recent years, urban residential water demand has continually grown with the rapid urbanization in China, which has been the main contributor to the increase of total urban water consumption. The fast growth of urban water consumption poses a great threat to urban water security and sustainable water resources management. To explore the dominant factors influencing the urban residential water consumption and further to propose the effective measures to control the fast growth of water consumption, this study selected the daily water consumption per capita (DWCC) as an indicator to quantitatively characterize the residential water consumption level and analyzed the spatial and temporal characteristics of DWCC in the period of 2005–2014 based on the data collected from 38 major cities in China. The results showed that the average values of DWCC in the 38 major cities were 141.9 L/d, 159.4 L/d and 129.3 L/d in 2005, 2010 and 2014 respectively. The urban residential water consumption showed a significant decreasing trend in the period of 2005–2014 due to the strategy of water-saving society construction in China. Meanwhile, the DWCC was showing a great spatial variability among different cities, which was much greater in southern cities than that in northern cities. The reason behind this is that the main influencing factors differ greatly among different cities. Based on the path analysis, we also identified the dominant factors influencing the DWCC from the 9 main possible factors. The amount of available water resources, the domestic water price and the usage rate of water-saving appliances are recognized as the dominant influencing factors. At last, the differential countermeasures are proposed to improve the urban water-saving management level and guarantee the urban water security in China.